Recent investigations at the prehistoric site RH-5 (Raʾs al-Ḥamrāʾ, Muscat, Sultanate of Oman) - Marcucci, Lapo Gianni; Genchi, Francesco; Badel, Émilie; Tosi, Maurizio (Proceedings of the Seminar for Arabian Studies, 2011)
After a gap of twenty years, the Italian Archaeological Mission in Oman has resumed excavations at the Middle Holocene site of Ra՚s al-Ḥamrā՚ 5 (RH-5), carrying out an intensive exploratory programme in three consecutive seasons, supported by the Ministry of Heritage & Culture, which aims to create an archaeological park. The resumption of the excavations at RH-5 has so far yielded new data that will give us precise details about the synchronie and diachronic dynamics of the area's population, and also about the economic and social dynamics of Neolithic societies in eastern Arabia. In this paper, we present the preliminary results of the recent excavations. In particular, we consider the spatial organization of the settlement, recovered by means of digital recording. The 2008 excavation season has disclosed new evidence concerning the settlement sequence, while work carried out in 2009 has yielded new information on dwelling types and household installations mostly from the earliest phase of the sequence, which can be dated to around the late fifth and early fourth millennia BCE. Furthermore, a comparison of the remains of the RH-5 settlement with those of contemporary sites so far investigated along the eastern shores of Arabia, along with the ethno-historical study of different populations, is considered to provide a better understanding of the spatial organization of the village in view of the future construction of the Ra's al-Hamra (Ra՚s al-Ḥamrā՚) Heritage Park.